Effects of supplementing a monoglyceride blend with salinomycin and a coccidosis vaccine on the growth performance and carcass characteristics of broiler chickens - Siriphong, Hutsanai; Prasongsook, Sombat; Rakangthong, Choawit; Rangubhet, K.Teepalak; Poeikhampha, Theerawit (Journal of Mahanakorn Veterinary Medicine, 2024)
This study aimed to compare the effects of supplementing monoglycerides blend on the growth performance of broiler chickens that received salinomycin (coccidiostat) and a coccidiosis vaccine.The experiment was conducted with 1,260 one-day-old ROSS 308 broilers and lasted for 35 days. A completely randomized design (CRD) was employed. All broilers were randomly assigned to six groups with 6 replicates per group and 35 broilers per replicate as follows: 1) control group (no supplementation of the monoglyceride blend and salinomycin), 2) coccidiosis vaccine group, 3) 0.006% salinomycin supplemented group, 4) 0.05% monoglyceride blend supplemented group, 5) coccidiosis vaccine and 0.05% monoglyceride blend group, and 6) salinomycin and 0.05% monoglyceride blend group. The results showed that the final body weight, weight gain, growth rate, and conversion rate to body weight of the group supplemented with salinomycin and monoglycerides blend were significantly better than the other (p<0.01). The supplement of a monoglycerides blend andsalinomycin in broiler chickens feed resulted in improving final body weight, body weight gain, growth rate, and feed conversion efficiency.However, it did not significantly affect carcass characteristics though it showed a tendency to increase the weight of the inner filet. Therefore, the supplementation of a monoglycerides blend with salinomycin and a coccidiosis vaccine in broiler chicken feed could improve growth performance in broiler chickens.